2006
DOI: 10.1152/ajpgi.00303.2005
|View full text |Cite
|
Sign up to set email alerts
|

Feline lower esophageal sphincter sling and circular muscles have different functional inhibitory neuronal responses

Abstract: The lower esophageal sphincter (LES) has a circular muscle component exhibiting spontaneous tone that is relaxed by nitric oxide (NO) and a low-tone sling muscle that contracts vigorously to cholinergic stimulation but with little or no evidence of NO responsiveness. This study dissected the responses of the sling muscle to nitrergic innervation in relationship to its cholinergic innervation and circular muscle responses. Motor responses were induced by electrical field stimulation (EFS; 1-30 Hz) of muscle str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
0
15
1
Order By: Relevance
“…Physiological 39,4244 , electrophysiological 8,11,12,16 , and immunohistochemical 14 investigations of the sling and cooperative LES muscle fibers have been focused largely on understanding the motor control of the tissues. Neuropharmacological therapies for GERD are most commonly designed either to ameliorate symptoms (proton pump inhibitors, mucosal protectants, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Physiological 39,4244 , electrophysiological 8,11,12,16 , and immunohistochemical 14 investigations of the sling and cooperative LES muscle fibers have been focused largely on understanding the motor control of the tissues. Neuropharmacological therapies for GERD are most commonly designed either to ameliorate symptoms (proton pump inhibitors, mucosal protectants, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Morphological studies mapping the regional distribution of myenteric neurons in the LOS showed a majority of inhibitory neurons in the clasp region. Unlike the inhibitory components, the cholinergic one is stronger in sling fibres ( L'Heureux et al , 2006 ; Farre et al , 2007a ). Similarly, the variation can be explained by different cholinergic innervation ( Yuan and Brookes, 1999 ) and/or different sensitivity of both sides of the LOS to muscarinic receptors agonists as it was commented above.…”
Section: Asymmetry Of the Inhibitory And Excitatory Neurotransmissionmentioning
confidence: 93%
“…This effect seems to be species dependent. In cat, rat and human ( Gonzalez et al , 2004 ; L'Heureux et al , 2006 ; Farre et al , 2007b ), NOS inhibitors do not affect the ‘off’ contraction. In vivo experiments in opossums and cats showed that N G‐nitro‐ L ‐arginine (i.v.)…”
Section: Nitric Oxidementioning
confidence: 98%
See 1 more Smart Citation
“…It has been recently recognized that three specialized groupings of muscle fibers underlie GES sphincteric function: a grouping of specialized circularly oriented smooth muscle fibers intrinsic to the esophageal wall normally 2–3 cm above the junction between the esophageal body and the gastric cardia, where lie two circularly oriented groupings of smooth muscle fibers at the upper margin of the gastric cardia. The neurophysiological control of tone in these two muscle groupings, and therefore the mechanophysiology, is very different from the intrinsic upper circular grouping . Complicating the sphincteric mechanophysiology further, there is a source of contact pressure external to the esophageal wall supplied by a grouping of skeletal diaphragmatic crural muscle fibers that angulate around the external esophagus from the inferior surface of the costal diaphragm connecting at the vertebrae.…”
Section: The Gastroesophageal Segmentmentioning
confidence: 99%